2018
DOI: 10.1111/echo.14223
|View full text |Cite
|
Sign up to set email alerts
|

Association between fragmented QRS complexes and left ventricular dysfunction in healthy smokers

Abstract: Objective Smoking is a known risk factor for cardiovascular diseases and may cause myocardial damage independently of coronary artery disease. Fragmented QRS (fQRS) is an important marker of myocardial fibrosis, while speckle‐tracking echocardiography is a method used to show subclinical left ventricle dysfunction. Methods Our study included 230 healthy individuals aged 18–40 years. The patients included were separated into two groups: those smokers (n = 130) and non‐smokers (n = 100). After that healthy smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
1
10
1
2
Order By: Relevance
“…In a recent study, a negative correlation was observed between pack‐year history and LV GLS 19 . Interestingly, we did not find a correlation between the amounts of cigarettes smoked and strain variables.…”
Section: Discussioncontrasting
confidence: 83%
“…In a recent study, a negative correlation was observed between pack‐year history and LV GLS 19 . Interestingly, we did not find a correlation between the amounts of cigarettes smoked and strain variables.…”
Section: Discussioncontrasting
confidence: 83%
“…The association of mortality with GLS was stronger than LVEF [37]. GLS, which is obtained by STE, measures myocardial deformations via tracing of speckles' displacement [5,16,38]. Reduction in absolute GLS value is an indicator of a myocardial disease in most cases and portends future adverse events [35].…”
Section: Discussionmentioning
confidence: 99%
“…Less than two decades ago, fragmentation of QRS complex (fQRS) was coined on 12-lead EKG [ 3 ]. Abnormal deflections in QRS morphology is simply known as fQRS which originates from conduction delay and disrupted ventricular depolarization due to myocardial scarring [ 4 , 5 ]. fQRS is found in several cardiovascular and non-cardiovascular disorders including structural heart diseases [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association of mortality with GLS was stronger than LVEF (38). GLS, which is obtained by STE, measures myocardial deformations via tracing of speckles' displacement (5,16,39). Reduction in absolute GLS value is an indicator of a myocardial disease in most cases and portends future adverse events (36).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal de ections in QRS morphology is simply known as fQRS which originates from conduction delay and disrupted ventricular depolarization due to myocardial scarring (4,5). fQRS is found in several cardiovascular and non-cardiovascular disorders including structural heart diseases (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%